2002
DOI: 10.1086/340049
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Spectrum of Blastomycosis Diagnosed at Manitoba Hospitals

Abstract: Blastomyces dermatitidis is a dimorphic fungus endemic to Canada and the United States. Few reports regarding blastomycosis in Canada have been published. We retrospectively reviewed the medical charts of 143 patients with confirmed cases of blastomycosis diagnosed in hospitals in Manitoba, Canada, from 1988 through 1999. The annual incidence rate of blastomycosis in Manitoba was 0.62 cases per 100,000 population, compared with 7.11 cases per 100,000 population in the Kenora, Ontario district. The average age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 17 publications
(18 reference statements)
6
109
1
Order By: Relevance
“…5 In this region, retrospective epidemiologic analysis has found that the symptomatic incidence rate is 7.11 cases per 100 000 people, or about five times the reported incidence rate in Mississipi and Wisconsin (1.3 and 1.4 cases per 100 000 people, respectively). 5,6 Blastomycosis is acquired by the inadvertent inhalation of conidia; these are produced by the mycelial form of the fungus, which exists in nature. 5,7 The infectious conidia are transformed in the lungs into the yeast form, causing clinical blastomycosis if the infection is not controlled by the cell-mediated immune response.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…5 In this region, retrospective epidemiologic analysis has found that the symptomatic incidence rate is 7.11 cases per 100 000 people, or about five times the reported incidence rate in Mississipi and Wisconsin (1.3 and 1.4 cases per 100 000 people, respectively). 5,6 Blastomycosis is acquired by the inadvertent inhalation of conidia; these are produced by the mycelial form of the fungus, which exists in nature. 5,7 The infectious conidia are transformed in the lungs into the yeast form, causing clinical blastomycosis if the infection is not controlled by the cell-mediated immune response.…”
Section: Discussionmentioning
confidence: 94%
“…4,5 Although uncommon, the disease is endemic to the Ohio and Mississippi River basins and in the Canadian provinces and American states that border the Great Lakes, and is hyperendemic in the area of northwestern Ontario surrounding Lake of the Woods (Kenora, Ontario). 5 In this region, retrospective epidemiologic analysis has found that the symptomatic incidence rate is 7.11 cases per 100 000 people, or about five times the reported incidence rate in Mississipi and Wisconsin (1.3 and 1.4 cases per 100 000 people, respectively). 5,6 Blastomycosis is acquired by the inadvertent inhalation of conidia; these are produced by the mycelial form of the fungus, which exists in nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It affects humans as well as animals. Soil, decaying vegetation are the common habitat of this disease and it is common along waterways [23] . The causative agent of blastomycosis is Blastomyces dermatitidis which is dimorphic fungus that develop as amould in the environment and as yeast in the tissue [24] .…”
Section: Blastomycosismentioning
confidence: 99%